DEVELOPMENT Pengembangan Bahan Ajar Materi Ekosistem Rawa Gambut Berbasis eLEMA - Sugeng Mashabhi; Elga Araina; Shanty Savitri; Fernando Pratama (Jurnal Ilmiah Kanderang Tingang, 2023)
Interactive digital media based on android application eLEMA (Electronic Learning Material) is the implementation of distance education through online internet networks, a solution for effective teaching and learning activities (KBM). Supporting Ecosystem Material, especially Peat Swamp Forest Ecosystems, which are still minimal. Development research using the Research and Development (R&D) model of Hannafin and Peck consists of 3 phases Analysis, Design, Develop/Implementation. The results of eLEMA-based digital teaching materials research produce products in the form of RPS, teaching materials, material supplements and LKM have fulfilled the components as learning devices and can be used in the learning process. Based on the results of validation from material experts, media experts and student responses with good criteria and feasible to use. The eLEMA application makes it easy for students to access materials online and offline